Developing Chatbot Conversational Systems & the Future Generation Enterprise Systems - Asfoura, Evan; Kassem, Gamal; Alhuthaifi, Belal; Belhaj, Fozi (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Conversational technology has recently emerged effectively; it helps people in communicating with smart devices such as smartphones by using human language. When they emerged, they enabled and assisted users to perform various functions such as gathering information, conducting transactions, having general conversations, and easily navigating web services and entertainment. They not only have an impact on people in general by improving customer service as they can provide answers to any inquiries but also facilitated navigation by assisting people with disabilities by interacting with a system that deals with voices or any other human language. In addition, recently they started to play a significant role in enterprise systems by supporting employees as they are assisted in learning the newly implemented system. As virtual assistants, they contribute to better accessibility, and acceptance, and also reduce the costs associated with customer service. This paper provides a chatbot system that helps the employees to learn how to deal with the newly installed ERP system flexibly and easily, which helps in solving one of the common problems that occur when switching to the ERP system.